In vivo molecular imaging and radionuclide (131I) therapy of human nasopharyngeal carcinoma cells transfected with a lentivirus expressing sodium iodide symporter. - Shuo Shi; Min Zhang; Rui Guo; Ying Miao; Jiajia Hu; Yun Xi; Biao Li (PLoS ONE, 2015)
INTRODUCTION:Despite recent improvements in the survival rates for nasopharyngeal carcinoma (NPC), novel treatment strategies are required to improve distant metastasis-free survival. The sodium iodine symporter (NIS) gene has been applied for in vivo imaging and cancer therapy. In this study, we examined the potential of NIS gene therapy as a therapeutic approach in NPC by performing non-invasive imaging using 125I and 131I therapy in vivo. METHODS:We constructed a lentiviral vector expressing NIS and enhanced green fluorescent protein (EGFP) under the control of the human elongation factor-1α (EF1α) promoter, and stably transfected the vector into CNE-2Z NPC cells to create CNE-2Z-NIS cells. CNE-2Z and CNE-2Z-NIS tumor xenografts were established in nude mice; 125I uptake, accumulation and efflux were measured using micro-SPECT/CT imaging; the therapeutic effects of treatment with 131I were assessed over 25 days by measuring tumor volume and immunohistochemical staining of the excised tumors. RESULTS:qPCR, immunofluorescence and Western blotting confirmed that CNE-2Z-NIS cells expressed high levels of NIS mRNA and protein. CNE-2Z-NIS cells and xenografts took up and accumulated significantly more 125I than CNE-2Z cells and xenografts. In vitro, 131I significantly reduced the clonogenic survival of CNE-2Z-NIS cells. In vivo, 131I effectively inhibited the growth of CNE-2Z-NIS xenografts. At the end of 131I therapy, CNE-2Z-NIS xenograft tumor cells expressed higher levels of NIS and caspase-3 and lower levels of Ki-67. CONCLUSION:Lentiviruses effectively delivered and mediated long-lasting expression of NIS in CNE-2Z cells which enabled uptake and accumulation of radioisotopes and provided a significant therapeutic effect in an in vivo model of NPC. NIS-mediated radioiodine treatment merits further investigation as a potentially effective, low toxicity therapeutic strategy for NPC.